1981
DOI: 10.1111/j.1365-2648.1981.tb03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding: success or failure

Abstract: Awareness of the important role of breast feeding in child health and the reproductive cycle, which is well documented elsewhere, necessitates an examination of the changing practice of breast feeding. This paper reviews these changing practices both in Western and developing societies, examines the problems which lead to lactation failure, and looks at factors related to success in breast feeding. In the light of the need for practical help for successful breast feeding. the present system of support both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…16,17,23,24 Our bivariate analysis results also found these demographic factors to be important. However, probably because this was a highly educated and motivated group of women with strong support at home, the multivariate analysis did not show the usual demographic variables to be statistically significant.…”
Section: Discussionsupporting
confidence: 64%
“…16,17,23,24 Our bivariate analysis results also found these demographic factors to be important. However, probably because this was a highly educated and motivated group of women with strong support at home, the multivariate analysis did not show the usual demographic variables to be statistically significant.…”
Section: Discussionsupporting
confidence: 64%
“…Studies Charles Sturt University, Bathurst NSW 2795, Australia mes which prenatal attitudes jmd demographic variables can predict breastfeeding at 3 months among women who choose to breastfeed and whether aspects of the obstetric or postnatal experience also contribute to reduction or termination of breastfeeding The incidence and duration of breastfeeding have been associated with greater age, income level and education (Dix 1991, Gunn 1984, Helhngs 1985, Hitchcock & Goy 1988, Janke 1988, Jones et al 1986, Rentschler 1991, Saunders & Garroll 1988 It seems that these women are more aware of the benefits of breastfeeding, have more realistic expectations of a baby's demands, and are more able to adapt their routines and schedules to suit the baby (Houston 1981) Different socio-economic groups tend to resource differently, with greater use of written information, such as books and magazines, by higher socioecononuc groups (Hitchcock & Coy 1988) Women of lower socio-economic status make greater use of fiiends and family as a resource (Rentschler 1991) Gonfiicting evidence on the effects of antenatal education may also relate to demographic variables While breastfeeding education has been shown to have a positive lnfiuence on the mcidence eind length of lactation (Whitely 1978, Wiles 1984, research conducted with women from low socio-economic groups demonstrated that education did increase knowledge but did not improve existing attitudes or duration of breastfeeding (Hill 1987, Kaplowitz & Olson 1983 A supportive sociai environment is important to successful breastfeedmg Those women who have partners who prefer breastfeeding to artificial feeding have a much higher success rate at both initiating and maintaining breastfeedmg (Femstem et al 1986, Janke 1988, Jones et al 1986 Partners who are not supportive of breastfeeding were found to think that breastfeeding is bad for breasts and interferes with sex (Freed et al 1992)…”
Section: Correspondence Dtm Tulhch School Of Social Sciences and Libmentioning
confidence: 99%
“…Breast milk has been recognized for many years as the hest food for infants under 6 months of age Aside from its nutritional benefits, breast milk has shown to be lmportcint m the prevention of allergies and has definite lmmunological advantages for the infant (Cunningham & Jelliffe 1991) In Australia approximately 84 3% of habies leaving hospital are fully breastfed but this figure drops off to aroimd 53 4% at 3 months and 40 9% at 6 months of age (Hitchcock & Coy 1988) Many workers and researchers in contact with mothers have noted that a mother's inability to breastfeed her mfant often leaves her with feelings of guilt and inadequacy at her 'failure' (Fahy & Holschier 1988, Helhngs 1985 and quite determined not to repeat her negative experience, even though she is aware of the advant^es of breast milk ijones etaJ 1986) Yet Houston (1981) noted that, m societies where breastfeeding is the cultural norm and few other options are available, 100% of mothers initiate breastfeeding and 98% are still breastfeeding the mfant well beyond 6 months In the light of these contrasts this study exam-…”
Section: Introductionmentioning
confidence: 99%
“…This situation differs from the Western experience, where during the 1960s and 1970s breastfeeding was often a painful and onerous procedure for the mother. Sore nipples and insufficient milk were common problems that made it hard for mothers to maintain breastfeeding for more than a couple of months (4,5). The reasons for terminating breastfeeding included insufficient milk, anxiety, lack of motivation, stress, inconvenience, interference with work or studies, and tiredness (6,7).…”
mentioning
confidence: 99%
“…couple of months (4,5). The reasons for terminating breastfeeding included insufficient milk, anxiety, lack of motivation, stress, inconvenience, interference with work or studies, and tiredness (6,7).…”
mentioning
confidence: 99%